El acceso y el uso indebido de la información tributaria como causales de destitución de los servidores del Servicio de Rentas Internas - Vilcacundo Chamorro, Xavier Raúl (2016)
The main points of analysis of this research, focus on the grounds for dismissal in the public sector in Ecuador, the sanctioning processes substantiated by unauthorized access to tax information for the period 2011 to 2013 in the SRI, years in which They produced facts concerning the issue and finally the relevance to determine the proportionality of disciplinary sanctions and develop a proposal for a legal reform that typifies as grounds for dismissal access and misuse of tax information.